COMPARISON OF FILLER TYPES IN POLYLACTIC ACID COMPOSITES FOR 3D PRINTING APPLICATIONS - Thongsang, Sirinthorn; Sontikaew, Somchoke; Kachapol, Kantisa; Kaewkate, Thanitra; Aunchanlung, Wongsakorn (MATTER: International Journal of Science and Technology, 2019)
This research is a comparison of the addition of different fillers in polylactic acid (PLA) affecting the three-dimensional printing technique and their properties. The fillers consist of Wood flour (WF), Talc (TC), Calcium Carbonate (CaCO3), Microballoon (MB) and Silicon Dioxide (SiO2). The 5%wt fillers were added into PLA to fabricate the filaments by single screw extruder. The specimens were fabricated by Fuse Deposition Modeling (FDM) technique. The effects of fillers on the physical, mechanical, flow, thermal and morphological properties of polymers were of interest. It was found that the 3D printed parts were completely in shape during fabrication. The 3D printed parts of PLA composites were a difference in color and texture, and exhibited a lower tensile strength than those with the neat PLA, except for the PLA/WF. The glass microballoons mixed-PLA composites gave the higher Young’s modulus compared to those with composites. The 3D printed parts of PLA/TC composites had greater flexural strength than that of neat PLA and PLA composites. The impact strength and melt flow rate of PLA/MB composites were higher than that of neat PLA and PLA composites. The Vicat softening point of PLA/MB was similar to neat PLA, while PLA/CaCO3, PLA/WF, PLA/TC and PLA/SiO2 was lower compared with neat PLA.